The Effect of Sleep Duration on the Risk of Unintentional Injury in Korean Adults - Yeon-Yong Kim; Un-Na Kim; Jin-Seok Lee; Jong-Heon Park (Korean Society for Preventive Medicine, 2014)
ObjectivesThe decrease or increase in sleep duration has recently been recognized as a risk factor for several diseases, including hypertension and obesity. Many studies have explored the relationship of decreased sleep durations and injuries, but few have examined the relationship between increased sleep duration and injury. The objective of this research is to identify the risk for injury associated with both decreased and increased sleep durations.MethodsData from the 2010 Community Health Survey were used in this study. We conducted logistic regression with average sleep duration as the independent variable, injury as a dependent variable, and controlling for age, sex, occupation, education, region (cities and provinces), smoking, alcohol use, body mass index, hypertension, diabetes, arthritis, and depression. Seven categories of sleep duration were established: ≤4, 5, 6, 7, 8, 9, and ≥10 hours.ResultsUsing 7 hours of sleep as the reference, the adjusted injury risk (odds ratio) for those sleeping a total of ≤4 h/d was 1.53; 1.28 for 5 hours, for 1.11 for 6 hours, 0.98 for 8 hours, 1.12 for 9 hours, and 1.48 for ≥10 hours. The difference in risk was statistically significant for each category except for the 8 and 9 hours. In this study, risk increased as the sleep duration decreased or increased, except for the 8 and 9 hours.ConclusionsThis research found that either a decrease or increase in sleep duration was associated with an increased risk for injury. The concept of proper sleep duration can be evaluated by its associated injury risk.